Capacity Building for Rural Health Care Providers in Cameroon using a Blended Learning approach – Experience of Koegni-eHealth - Kouematchoua, Ghislain; Kemloh Wagoum, Armel Ulrich; Nguento, Alain; Bouwa, Marcel; Kom Kenmegne, Gilles; Scolard, Xavier (Journal of Health Informatics in Africa, 2013)
Background and objectives: The health system in Cameroon has to deal with a drastic shortage of professionals in rural areas. This is an obstacle to a good and adequate health care delivery in these areas. Accordingly, the few clinicians who are available, the patients (and their relations) and other active players need support throughout the care process. For this reason, we developed capacity building programs that prepare rural health care providers to efficiently deal with the increasingly number of new (for African countries) health challenges.Methods: A review of the relevant research literature and project report has been performed. A Stakeholder analysis was conducted using unstructured interviews methods. Profiles and infrastructure analysis were conducted and key requirements identified. Based on these, German certification Curricula were adapted and implemented using the virtual environment of Koegni-eHealth, the expertise of the African Diaspora and a mixture of e-learning and face-to-face theoretical and practical courses. An implementation plan and evaluation indicators were formulated. Agile methods (SCRUM and KANBAN) and quality management processes were applied for the project management (including change management)